2019
DOI: 10.1029/2018tc005276
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Crustal and Uppermost Mantle Structures Across Eastern Tibet and Adjacent Regions: Implications of Crustal Flow and Asthenospheric Upwelling Combined for Expansions of the Tibetan Plateau

Abstract: We present new, high‐resolution constraints on crustal and uppermost mantle structure of the southeastern, eastern, and northeastern Tibetan plateau and adjacent regions by combining extensive data from three regional‐scale dense seismic arrays. Our results show significant differences in the crustal and uppermost mantle structure within the Songpan‐Ganzi terrane. The southern part has a thick crust and high Poisson's ratio, while the crustal thickness becomes less and Poisson's ratio is nearly normal in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…F. Zhang et al (2018b) observed high S-wave velocity from the upper crust to 300 km based on teleseismic travel-time tomography over the stations by the ChinArray-I and II projects. C. Zheng et al (2019) obtained lower S-wave velocity from 30 km to 100 km beneath the Chuandian fragment than beneath the Sichuan basin based on the joint inversion of receiver function and dispersion curves by the same data. Xin et al (2019) observed high P-wave velocities from 100 to 150 km depth beneath Chuandian with local-earthquake body-wave tomography, but S-wave velocities were not anomalous over the same depth interval.…”
Section: The Sichuan Basin and Chuandian Fragmentmentioning
confidence: 88%
“…F. Zhang et al (2018b) observed high S-wave velocity from the upper crust to 300 km based on teleseismic travel-time tomography over the stations by the ChinArray-I and II projects. C. Zheng et al (2019) obtained lower S-wave velocity from 30 km to 100 km beneath the Chuandian fragment than beneath the Sichuan basin based on the joint inversion of receiver function and dispersion curves by the same data. Xin et al (2019) observed high P-wave velocities from 100 to 150 km depth beneath Chuandian with local-earthquake body-wave tomography, but S-wave velocities were not anomalous over the same depth interval.…”
Section: The Sichuan Basin and Chuandian Fragmentmentioning
confidence: 88%
“…(2000), the terrestrial heat flow value of the TP is high. Reflection and refraction investigations (M. Liu et al., 2006; Z. Zhang et al., 2013) and Poisson's ratio (C. Zheng et al., 2019) indicate that the chemical composition is rather felsic in the mid‐lower crust of the QLOB, and felsic rocks are usually weaker than intermediate/mafic rocks under the same temperature and pressure conditions (Wilks & Carter, 1990). High heat flow and more felsic composition could weaken the mid‐lower crust in the QLOB, resulting in decoupling of the upper and lower crust, as described above.…”
Section: Discussionmentioning
confidence: 99%
“…Anisotropy results using the Ps phase in receiver functions (Xie et al., 2017) show that the crustal anisotropy in the QLOB is consistent with the GPS velocity field (Gan et al., 2007; M. Wang & Shen, 2020) but differs from the direction of the XKS splitting results (Chang et al., 2015; Wuestefeld et al., 2009), indicating that there may be a crustal low‐velocity layer. Some seismic tomography studies have revealed a remarkable mid‐crust low‐velocity zone (LVZ) with a thickness of ∼20 km in the QLOB (Bao et al., 2013; Jiang et al., 2014; H. Li, Shen, et al., 2014), while others have not (Y. Li et al., 2017; C. Zheng et al., 2019). The ambiguity is caused by the fact that most of these images focus on the large‐scale structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a few other explanations about the origin of the low‐V zones beneath NE Tibet, such as that related to the detachment of the crust due to interaction with adjacent blocks (Gao et al, 2019; Liu et al, 2008; Sun et al, 2019), fluids resulting from dehydration of hydrous minerals in the deeper crust and uppermost mantle (Cheng et al, 2016), or upwelling flow in the big mantle wedge due to deep subduction of the Indian plate down to the mantle transition zone (e.g., Hearn et al, 2019; Lei et al, 2019; Lei & Zhao, 2016; Zheng et al, 2019), because the Indian slab has moved horizontally to the Kunlun mountain in the mantle transition zone (Hu et al, 2013; Lei et al, 2019; Lei & Zhao, 2016; Shen et al, 2011). All the previous results support our present anisotropic tomography of the crust and uppermost mantle.…”
Section: Discussionmentioning
confidence: 99%